Differential Leukocyte and Platelet Counts as Early Diagnostic Indicators in Acute Dengue Infection - Alishba Naeem, Maryam Zahra, Sehar Khaliq, Alishba Naeem, Maryam Zahra, Sehar Khaliq (Journal of Rawalpindi Medical College, 2022)
Background: Dengue is an epidemic in Pakistan. Proper monitoring of dengue cases is necessary for its early diagnosis and prevention especially in developing countries with limited resources. Our study aims to use some hematological parameters as Early Diagnostic Indicators in Acute Dengue Infection which can help in reducing mortality and morbidity. Methods: Dengue NS1 Antigen test was used to identify 119 Dengue Patients over the months of August-October, 2019. Hematological data from such patients was collected and analysed. Results: In our study thrombocytopenia was prominent with sensitivity based on gender distribution being 86% for males and 76% for females. According to age, distribution thrombocytopenia had a sensitivity of up to 81% in the younger age group and 80% in the older age group. The other prominent findings in younger age groups were lymphopenia, neutropenia, and monocytopenia with a sensitivity of 55%, 43%, and 24% respectively. Lymphopenia and neutropenia had similar sensitivity across the two genders, whereas monocytopenia had higher sensitivity among females of 27% as opposed to males of 12%. Eosinopenia did not differ as much among the two age groups i.e. 18% in young and 19% in older patients and across the two genders i.e. 56% in males and 60% in females. The sensitivity of lymphocytosis in older patients is 21% which was also significant. Conclusions: The Differential Leukocyte Count and Platelets Count can help as an early indicators of acute dengue infection in resource limited areas. This can help in early diagnosis and prompt treatment thus reducing complications. Keywords: Acute dengue, differential leukocyte count, platelets count, thrombocytopenia, neutropenia